Manajemen Kegiatan Parenting dalam Membentuk Karakter Anak - Fatimatuz Zahro (Yayasan Avicenna, 2022)
This study aims to analyze the management of parenting activities in shaping the character of early childhood at the Taman Posyandu Anak Shalih. The research method used is a qualitative case study type. In order to get an idea of ​​the Management of Parenting Activities in Shaping Early Childhood Character, the researchers conducted interviews with principals and teachers at Taman Posyandu Anak Salih Nurul Jadid. The results of the study indicate that the formation of children's character requires a continuous and consistent process, for that schools build good cooperation with children's parents in the formation and development of children's character. In order to create integration between the formation of children's character at school with the formation of children's character at home. So schools approach parents through parenting activities, so that parents really become partners in children's education. So that parents can also maximize their role in the formation of children's character.